Association of PTPN22+1858C/T polymorphism with Type 1 diabetes in the North Indian population. (10th June 2014) - Kumar, N.; Kaur, G.; Kanga, U.; Tandon, N.; Caillat‐Zucman, S.; Mehra, N. K.
Summary A nonsynonymous SNP +1858C/T (rs2476601) in the protein tyrosine phosphatase, nonreceptor type 22(PTPN22) gene leading to Arg 620 Trp substitution is known to be associated with susceptibility to type 1 diabetes (T1D) and several other autoimmune diseases. We studied this polymorphism in 145 T1D patients and 210 healthy controls from North India. The minor allele +1858T was observed to be significantly increased among patients as compared to healthy controls (2.76% vs 0.5%, P = 0.027, OR = 5.93; 95% CI = 1.4–24.8). The association was also observed at the level of heterozygous C/T genotype (5.5% vs 0.95%, P = 0.026, OR = 6.07; 95% CI = 1.43–25.6). The T allele and C/T genotype were predominantly found among patients who were positive for both glutamic acid decarboxylase 65 (GAD65) and insulin antigen 2 (IA2) autoantibodies and showed significantly increased frequencies (10%, P = 0.034, OR = 11.67; 95% CI = 1.58–84.1 and 20%, P = 0.031, OR = 13.0; 95% CI = 1.66–97.5, respectively) as compared to patients negative for these autoantibodies (0.95% and 1.9%, respectively). The results suggest that the PTPN22+1858T allele is positively associated with T1D in the North Indian population.